The use of virtual reality glasses and their effect on learning the skill of jumping on vault among students of the Open Educational College - Lifta, Iqbal Ammar (International Journal of Psychosocial Rehabilitation, 2020)
Gymnastics events are popular mass games in most world counties. It is a game of competitive nature of interest to followers and practitioners. The development in this game from the physical and skill aspects came as a result of the development in various sciences sports. The development in modern teaching methods in the field of sports science in general opens new horizons and modern ways in the teaching process toward improving the physical ability and skill of sports. The use of virtual reality in learning the skill of jumping on vault, which is characterized by the difficulty of learning its skill by the students, is necessitating care to choose appropriate teaching methods, In order to improve the physical capabilities and skills of students. Each teaching method has its own goals, characteristics, contents, and applications which suit the skill to be learned. Furthermore, learning methods must be suitable for the ages, study stage, and takes into account the individual differences of learners, the educational environment, and its possibilities and needs to be consistent to be achieved.